Literasi Hadis Tentang Larangan Marah - N, Nurmadia; R, Risdahyanti; Sakka, Abdul Rahman; Khalik, Subehan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to discuss the hadith regarding the prohibition of anger. The Prophet SAW, forbade someone from getting angry with a lot of history. When viewed from a health aspect, expressing anger or holding it in both have harmful effects on health. This is what is interesting to study the hadith of the Prophet SAW which prohibits anger in more depth, so that it can provide more knowledge about anger, as well as answer questions that arise from the impression of contradiction that arises regarding the permissibility and prohibition of anger. This research uses qualitative methods through literature study applying the hadith takhrij and hadith sharia methods through in-depth analysis of the hadith based on relevant context and interpretation to understand the meaning contained in the hadith. Based on this research, it was found that (1) The hadith studied had 9 hadith lines, using the lidwah library application. (2) the quality of the hadith regarding the prohibition of anger, namely that it has authentic status because it is contained in the Sahih written by al-Bukhari where this book meets the special criteria as determined by the author. (3) The meaning of the hadith which is the object of study is that the prohibition against anger applies to all human beings. and anger is permitted on matters involving religious matters.